Rabbinic Judaism - Reif, Stefan C. 1944- (2020)
In the second Temple period, Jewish ritual and worship, following the example of the Hebrew Bible, centered on the cult of the Jerusalem Temple and on the more democratic institution of individual prayer, but the two elements had drawn closer to each other by the axial age. In their campaign to establish formal communal prayer as a theological priority, leading rabbis of the first two centuries were inspired not only by those two precedents but also by biblical formulas, the example set at Qumran, the notion of the berakhah, and by the development of the synagogue, which added prayer to its earlier interest in study, social activity, and the hosting of visitors. The shema’, ‘amidah, and birkat ha-mazon, as well as qiddush, havdalah, hallel, and the Passover Haggadah, were early components of rabbinic liturgy, and these gradually moved from the domestic and individual contexts to the synagogue and community. Towards the end of the talmudic period, liturgical poetry and mysticism, especially from the Jewish homeland, were incorporated into standard rabbinic prayers, but not until the ninth and tenth centuries did rabbinic leaders in Babylonia succeed in transforming the oral prayers into the written prayer-book. Although use was limited of the Hebrew Bible and lists of sacrifices from the earliest rabbinic liturgy, such scriptural readings acquired a more important, structured role in the late talmudic, post-talmudic, and early medieval periods. Although the temple service and priesthood figured in the liturgical poems, they had lost much of their status as spiritual intermediaries.